The Role of Animal Serum Bank in Investigating Animal Diseases by Seroepidemiological and Retrospective Studies - Indrawati Sendow (Indonesian Center for Animal Research and Development, 2012)
Serum bank is a place to collect sera from random collection as a representative population for a long period and still maintain its characteristic of biochemical and immunological aspects. Serum Bank can store many sera from different species of animals from different areas. National and regional serological surveys can be done relatively in short period, without the need of skilled human resources and budget to collect the sera from the field. Hence, the basic information or seroepidemiological and retrospective studies can be obtained within in a short time. Serum Bank at Research Institute for Veterinary Science (RIVS) consists of survey and sentinel collections which were conducted by RIVS staffs, regional livestock services, Disease Investigation Center and farmers. This paper will describe the role, management, the advantages of Bank Serum and its problem. Due to its importance, Serum Bank needs to be maintained to keep its function for other purposes. Key words: Serum Bank, serum collection, animal diseases